CITIZENSHIP FROM TRASH: VALUING PEOPLE AND WASTE AS AN INFLECTION IN THE HISTORICAL SOCIO-SPATIAL FRAGMENTATION OF BOGOTÁ - Calil, Thiago Godoi [UNESP]; Murillo-Paredes, Axel (Editorial Universidad de Sevilla, 2025)
Bogotá currently has approximately 8 million inhabitants, with a daily production of approximately 10,000 tons of garbage. Of these millions of people, it is estimated that over 10,000 live on the streets in conditions of extreme vulnerability. Many survive through informal, and sometimes illicit dynamics, and the practice of recycling is quite common, fundamentally contributing to the reuse of approximately 2,000 tons per day. Through documentary and media research, an exploratory bibliographic review and field observation, this text seeks to establish this connection between the reality of homeless people, garbage, the importance of recycling and the policies for managing human and non-human waste in the city of Bogotá, as these are challenged in the social representation and symbolism associated with them. As a result, we seek possibilities for a fundamental change in the way life is carried out in Bogotá, through an association between the street, drugs and waste management, in which people who interact with these aspects take on the role of caring for their lives and the urban community.
CIUDADANÍA DESDE LA BASURA: VALORANDO A LAS PERSONAS Y LOS RESIDUOS COMO INFLEXIÓN EN LA FRAGMENTACIÓN SOCIOESPACIAL HISTÓRICA DE BOGOTÁ
CIDADANIA VINDA DO LIXO - VALORIZANDO PESSOAS E RESÍDUOS COMO INFLEXÃO NO PROCESSO DE FRAGMENTAÇÃO SOCIOESPACIAL EM BOGOTÁ
Keywords: citizenship; garbage; inequality; socio-spatial fragmentation; waste management